Economic Role of Zakat in Reducing Income Inequality and Poverty in Selangor - Ibrahim, Patmawati (2006)
This study attempts to examine the economic role of zakat as a mechanism to reduce income inequalities and poverty in the state of Selangor. The target population of this study is the fuqara and masakin categories of the Pusat Zakat Selangor (PZS) zakat recipients. Purposive sampling procedure is applied to collect primary data related to zakat recipients from the poor and needy category of the nine districts of Selangor. Inequality and poverty maps are derived based on the collected data. These facilitate an examination of the most affected area of income inequality and an analysis of poverty within the context of selected socio economic variables. The effects of zakat distribution on income inequality and welfare loss are examined by using Lorenz curve, Gini coefficient, and the Atkinson index. The first two measures make no explicit use of any concept of social welfare represent a positive measure. The Atkinson index which represents a normative measure of inequality, takes into account, the social welfare and income loss incurred from unequal income distribution. The effects of zakat distribution on poverty are analyzed within the context of burden of poverty; specifically in terms of incidence, intensity and severity of poverty. These are examined using five major indices of poverty, which include the household count ratio, average poverty gap, income gap, Sen index and FGT index. Empirical findings of the positive measures of the Lorenz curve and Gini coefficient indicate the positive contributions of zakat distribution in reducing income inequality. However results related to the Atkinson index show that the current practice of zakat distribution increases income inequality, increases income loss, and reduces social welfare. On a positive note though, the analysis reveal that zakat distribution reduces poverty incidence, reduces the extent of poverty and lessens the severity of poverty. Hence, experimenting five simulations pertaining to the different models of zakat distribution in attempt to offer alternative zakat distribution model in terms of greatest reduction in income inequality and maximization of social welfare extend this study. The best model of zakat distribution identified is based on had-kifayah. The above findings together with the identification of the group most affected by income inequality and poverty will pave the way towards policies for a more effective and efficient utilization of scarce zakat resources.